2006
DOI: 10.1097/01.ajp.0000210932.27945.4a
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-controlled Study of Fentanyl Buccal Tablet for Breakthrough Pain in Opioid-treated Patients With Cancer

Abstract: FBT is efficacious and safe in the treatment of cancer-related BTP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
167
1
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(192 citation statements)
references
References 24 publications
16
167
1
8
Order By: Relevance
“…The pattern of AEs and the number of patient deaths during the study are reflective of the underlying disease states of the patients. The AEs judged to be related to INFS included vomiting, dizziness, fatigue and euphoric mood, all of which are commonly observed with the use of rapid onset opioid analgesics in this indication [16,42,43], as well as rhinalgia and sneezing attributable to the intranasal mode of drug delivery. The lower frequency of AEs observed in the current study, compared with those reported in controlled studies [16][17][18], may in part reflect the shorter duration of this study, as well as differences in reporting procedures and study design.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of AEs and the number of patient deaths during the study are reflective of the underlying disease states of the patients. The AEs judged to be related to INFS included vomiting, dizziness, fatigue and euphoric mood, all of which are commonly observed with the use of rapid onset opioid analgesics in this indication [16,42,43], as well as rhinalgia and sneezing attributable to the intranasal mode of drug delivery. The lower frequency of AEs observed in the current study, compared with those reported in controlled studies [16][17][18], may in part reflect the shorter duration of this study, as well as differences in reporting procedures and study design.…”
Section: Discussionmentioning
confidence: 99%
“…Pain relief has been observed to begin as early as 10 minutes after administration and to last throughout the 120-minute observation period 64 . In two randomized controlled trials that compared fentanyl buccal tablets with placebo, btcp relief attained significantly favoured fentanyl buccal tablets 64,65 .…”
Section: Contemporary Approaches To the Management Of Btcp With Rapidmentioning
confidence: 98%
“…In a randomized placebo-controlled study of fentanyl sublingual tablets in 131 adult patients with btcp, use of the tablets resulted in significant improvements in pain intensity and relief compared with placebo 66 . In phase iii studies evaluating the long-term effectiveness of transmucosal immediate-release fentanyl, patients reported high levels of satisfaction with the formulation 65,67 .…”
Section: Contemporary Approaches To the Management Of Btcp With Rapidmentioning
confidence: 99%
See 1 more Smart Citation
“…Availability of FBT was 48%, in comparison with 22% of OTFC. Controlled studies have shown that FBT is effective in treating breakthrough cancer pain [32].…”
Section: New Delivery Systemsmentioning
confidence: 99%